Recent Advances of Chinese Palaeoanthropology - Wu, Rukang (Occasional papers' series (Hong Kong University Press) ;, 1982)
The Hong Kong University Press Occasional Papers' Series is an entirely new series of monographs encompassing the best lectures presented to the University of Hong Kong in recent times.